Interaction Effect of Organizational Value on Corporate Social Responsibility Practices of Indian SME’S (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to discuss the interaction between corporate social responsibility (CSR) and organizational identity (OI). This research examines whether perceived internal CSR mediates the link between overall CSR dimension and OI. Researchers also investigate how organizational value (OV) moderates this mediated relationship. The cross-sectional analysis explores the relationship between perceived internal CSR (PICSR) and the overall CSR component and OI. Organizational value moderates the relationship between overall CSR dimension and PICSR but not the relationship between PICSR and organizational identity. The findings were optimistic when tracking the CSR component of the community, employees, consumers, and the environment. The results show that the overall CSR dimension provides a clear sense of internal CSR and organizational values as core values.